Pulmonary alveolar proteinosis (PAP) in idiopathic hypoparathyroidism - Saha, Soma (BMJ Case Rep, 2019)
Idiopathic hypoparathyroidism (IH) and autoimmune pulmonary alveolar proteinosis (PAP) are rare disorders. A patient with IH and optimal calcaemic control on calcium and alfacalcidol was detected to have PAP after 8 years of follow-up. Patient had no respiratory complaints. Routine abdominal imaging for renal calcification showed patchy ground glass opacities in the lower lung fields leading to incidental diagnosis of PAP. Pulmonary function tests showed impaired diffusion capacity of the lung. Anti-granulocyte macrophage-colony stimulating factor autoantibodies were positive. Patient regularly attended the pulmonary clinic and showed progressive improvement in diffusion capacity of the lung during 2 years of follow-up. The calcaemic control in IH remained stable despite its presence with PAP. The autoimmune PAP in the presented case suggests a possible autoimmune basis of IH.